Collaborative Strategies for Improving the Human Development Index - Mousche Willems Jullians Woria; Akmal Ibrahim; Hasniati Hasniati; Didik Iskandar (Borong Newinera Publisher, 2026)
Cross-sectoral collaboration in improving the Human Development Index (HDI) requires not only the involvement of stakeholders but also a well-defined collaborative strategy to ensure effective cooperation. However, in practice in Tambrauw Regency, such a collaborative strategy has not yet been clearly formulated, resulting in development programmes being implemented in a fragmented and uncoordinated manner. This study aims to analyse collaborative strategies in cross-sectoral collaboration for improving the HDI in Tambrauw Regency. Methodology. The study employs a qualitative approach using a case study methodology. Data were collected through interviews, observations, and documentation, and analysed using an interactive model. The findings indicate that the formation of cross-sectoral partnerships has not been carried out systematically and remains dependent on the needs of specific programmes. The formulation of joint strategies has not yet been carried out collectively, meaning that each organisation continues to implement programmes based on its own sectoral interests. The implementation of collaborative strategies has not yet been carried out jointly, but rather in a piecemeal manner within each organisation. Furthermore, the implementation of strategies at the organisational level has not been aligned in a single direction, thus failing to generate strong synergies. This situation has resulted in suboptimal outcomes from collaborative strategies in improving the Human Development Index (HDI), as the programmes being implemented do not yet support one another and are unable to address issues comprehensively. Collaborative strategies within cross-sectoral collaboration in Tambrauw Regency have not been effective because they have not been formulated and implemented jointly; consequently, there is a need to strengthen integrated collaborative strategic planning that is oriented towards shared objectives.